Are we ready for genetic testing for primary open-angle glaucoma?. (May 2018) - Khawaja, Anthony; Viswanathan, Ananth
Abstract Following a dramatic reduction in the cost of genotyping technology in recent years, there have been significant advances in the understanding of the genetic basis of glaucoma. Glaucoma patients represent around a quarter of all outpatient activity in the UK hospital eye service and are a huge burden for the National Health Service. A potential benefit of genetic testing is personalised glaucoma management, allowing direction of our limited healthcare resources to the glaucoma patients who most need it. Our review aims to summarise recent discoveries in the field of glaucoma genetics and to discuss their potential clinical utility. While genome-wide association studies have now identified over ten genes associated with primary open-angle glaucoma (POAG), individually, variants in these genes are not predictive of POAG in populations. There are data suggesting some of these POAG variants are associated with conversion from ocular hypertension to POAG and visual field progression among POAG patients. However, these studies have not been replicated yet and such genetic testing is not currently justified in clinical care. In contrast, genetic testing for inherited early-onset disease in relatives of POAG patients with a known genetic mutation is of clear benefit; this can support either regular review to commence early treatment when the disease develops, or discharge from ophthalmology services of relatives who do not carry the mutation. Genetic testing for POAG at a population level is not currently justified.